Signaling Mechanisms of Stem Cell Therapy for Intervertebral Disc Degeneration - Xiaotian Du; Kejiong Liang; Shili Ding; Haifei Shi (Biomedicines, 2023)
Low back pain is the leading cause of disability worldwide. Intervertebral disc degeneration (IDD) is the primary clinical risk factor for low back pain and the pathological cause of disc herniation, spinal stenosis, and spinal deformity. A possible approach to improve the clinical practice of IDD-related diseases is to incorporate biomarkers in diagnosis, therapeutic intervention, and prognosis prediction. IDD pathology is still unclear. Regarding molecular mechanisms, cellular signaling pathways constitute a complex network of signaling pathways that coordinate cell survival, proliferation, differentiation, and metabolism. Recently, stem cells have shown great potential in clinical applications for IDD. In this review, the roles of multiple signaling pathways and related stem cell treatment in IDD are summarized and described. This review seeks to investigate the mechanisms and potential therapeutic effects of stem cells in IDD and identify new therapeutic treatments for IDD-related disorders.